The Keys to Successful SOAs aligning business and technology to achieve enterprise goals. - Liebow, Michael (SOA webservices journal.)
Today most of the conversations surrounding service-oriented architectures (SOAs) focus on flexibility and breaking down applications into services : modular, reusable, componentized, with increased availability to the services as well as increased management of them. However, with these conversations comes the risk of getting sucked into a technology-centric vacuum in which consideration for the real business problems that customers need to solve might be neglected.